1995
DOI: 10.1002/jlb.58.3.359
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, and functional characterization of rat MIP-2: a neutrophil chemoattractant and epithelial cell mitogen

Abstract: Macrophage inflammatory protein-2 (MIP-2) is a member of a family of cytokines that play roles in inflammatory, immune, and wound healing responses. To clone the cDNA for rat MIP-2, RNA was isolated from the lungs of Fischer 344 rats after instillation of lipopolysaccharide. Reverse transcription-polymerase chain reaction was performed by using synthetic oligonucleotide primers designed from the mouse MIP-2 cDNA sequence. A cDNA containing the coding region of rat MIP-2 was cloned and sequenced. Comparison to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(88 citation statements)
references
References 16 publications
4
81
0
2
Order By: Relevance
“…It is therefore reasonable to speculate that soluble factors produced by activated macrophages trigger additional cells types, such as epithelial cells and leukocytes, thus provoking an inflammatory cascade. A related observation is the induction of MIP-2 by chitosan, since Driscoll and colleagues have reported that MIP-2 stimulates epithelial cell proliferation [8]. Hence, MIP-2 production by activated macrophages may play a critical role in epithelial regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore reasonable to speculate that soluble factors produced by activated macrophages trigger additional cells types, such as epithelial cells and leukocytes, thus provoking an inflammatory cascade. A related observation is the induction of MIP-2 by chitosan, since Driscoll and colleagues have reported that MIP-2 stimulates epithelial cell proliferation [8]. Hence, MIP-2 production by activated macrophages may play a critical role in epithelial regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse transcription. A 1-g portion of total RNA was subjected to first-strand cDNA synthesis in a 25-l reaction mixture containing avian myeloblastosis virus reverse transcriptase (10 U), dNTP mixture (2 mM concentrations of each dNTP), oligo(dT) [12][13][14][15][16][17][18] primers (10 M), and reaction buffer as supplied with the enzyme (50 mM Tris-HCl (pH 8.3), 50 mM KCl, 10 mM MgCl 2 , 0.5 mM spermidine, and 10 mM DDT). The samples were incubated in a PerkinElmer 480 thermal cycler (PerkinElmer, Wellesley, MA) at 42°C for 60 min followed by enzyme denaturation step at 94°C for 2 min.…”
Section: Lung Cytokine Gene Expression (Rt-pcr)mentioning
confidence: 99%
“…Within the CXC chemokine subfamily, the presence of a glutamate-leucine-arginine (ELR) motif before the first conserved cysteine residue confers selectivity in recruiting neutrophils (30), and the ELR-containing CXC chemokines, CINC, and MIP-2 are potent inducers of neutrophil activation and their directional migration (17,18,(31)(32)(33). We have therefore investigated whether the effect of ebselen on neutrophil recruitment might be achieved through inhibition of the macrophage CXC chemokines CINC-1 and MIP-2.…”
Section: Effect Of Ebselen On Airway CXC Chemokine Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10] Similarly, ENA-78 and MIP-2 are also produced by many cell types in response to TNF. [11][12][13][14] Recently, both Herbert and associates and ClarkLewis and colleagues have shown an important amino acid sequence in the primary CXC chemokine structure that appears to account for the disparate abilities of these molecules to function as promoters or inhibitors of neutrophil chemotaxis. [15][16][17] The 3 amino acid residues that immediately precede the first cysteine amino acid are critically important in receptor binding and neutrophil activation.…”
Section: -445)mentioning
confidence: 99%